Type 2 Neural Progenitor Cell Activation Drives Reactive Neurogenesis after Binge-Like Alcohol Exposure in Adolescent Male Rats - Nickell, Chelsea R. Geil; Peng, Hui; Hayes, Dayna M.; Chen, Kevin Y.; McClain, Justin A.; Nixon, Kimberly (Frontiers in Psychiatry, 2017)
Excessive alcohol consumption during adolescence remains a significant health concern as alcohol drinking during adolescence increases the likelihood of an alcohol use disorder in adulthood by four-fold. Binge drinking in adolescence is a particular problem as binge-pattern consumption is the biggest predictor of neurodegeneration from alcohol and adolescents are particularly susceptible to the damaging effects of alcohol. The adolescent hippocampus, in particular, is highly susceptible to alcohol-induced structural and functional effects, including volume and neuron loss. However, hippocampal structure and function may recover with abstinence and, like in adults, a reactive burst in hippocampal neurogenesis in abstinence may contribute to that recovery. As the mechanism of this reactive neurogenesis is not known, the current study investigated potential mechanisms of reactive neurogenesis in binge alcohol exposure in adolescent, male rats. In a screen for cell cycle perturbation, a dramatic increase in the number of cells in all phases of the cycle was observed at 7 days following binge ethanol exposure as compared to controls. However, the proportion of cells in each phase was not different between ethanol-exposed rats and controls, indicating that cell cycle dynamics are not responsible for the reactive burst in neurogenesis. Instead, the marked increase in hippocampal proliferation was shown to be due to a two-fold increase in proliferating progenitor cells, specifically an increase in cells co-labeled with the progenitor cell marker Sox2 and S-phase (proliferation) marker, BrdU, in ethanol-exposed rats. To further characterize the individual subtypes of neural progenitor cells affected by adolescent binge ethanol exposure, a fluorescent quadruple labeling technique was utilized to differentiate Type-1, -2a, -2b and -3 progenitor cells simultaneously. At one week into abstinence, animals in the ethanol exposure groups had an increase in proliferating type-2 (intermediate progenitors) and type-3 (neuroblast) progenitors but not type-1 neural stem cells. These results together suggest that activation of type 2 neural progenitor cells out of quiescence is likely the primary mechanism for reactive hippocampal neurogenesis following adolescent alcohol exposure.